Understanding Factors That Affect Level of Oral Communication Apprehension between Accounting and Non-Accounting Students: A Literature Review - Shaharuddin, Shahida; Md Nawi, Farah Amalina; Mansor, Maslina (GlobalIlluminators Publishing, 2015)
In the global and dynamic owrld, accountants are expedted to have more than academic knowledge. One of the important skilss needed by employer is effective communication. However prior research find that there is a trait to that which known as communication apprehension (CA). Most of the students shows that accounting students suffer highe level of CA as compared to non-accounting students. Accordingly, this paper aim to review existing research to discover the factors that affect level of Ca among accounting and non-contribute to thje higher level of CA. This study is expected to contribute to the discipline of knowledge especially in the field of social science by focusing to the current issues and challenges in educational environment. it is also assist to improve skills in the areas of teaching, learning dan also help to improve accounting curriculum.